Hubungan Status Gizi dengan Tumbuh Kembang pada Anak Usia 2-5 Tahun di Wilayah Kerja Puskesmas Limapuluh Kota Pekanbaru - Yulnefia Yulnefia; Ari Diansyah; Muhammad Naufal Makarim (Lembaga Pengembangan Kinerja Dosen, 2026)
Background The growth and development phase of children aged 2–5 years is crucial as it determines their future physical, mental, and behavioral outcomes. Wasting, stunting, and underweight remain major nutritional problems among young children, significantly affecting their development. In Pekanbaru City, particularly at Limapuluh Public Health Center, the prevalence of stunting is 5.16%, wasting 11.94%, and underweight 17.1%. These conditions highlight the importance of studying the relationship between nutritional status and child development in this critical age group.Objective To determine the relationship between nutritional status and development in children aged 2–5 years at Limapuluh Public Health Center, Pekanbaru.Methods This study employed an analytical observational design with a cross-sectional approach. The research was conducted at Limapuluh Public Health Center, Pekanbaru. Samples were obtained using accidental sampling, with primary data collected according to inclusion criteria. Data were analyzed using Spearman’s rank correlation test.Result : Among 88 children aged 2–5 years, most had normal nutritional status (75.0%) and normal development (87.5%). Spearman’s test revealed a strong positive correlation between nutritional status and child development (r = 0.682; p < 0.001).Conclusion There is a strong and significant positive relationship between nutritional status and development in children aged 2–5 years; the better the nutritional status, the more optimal the child’s development.